Interannual to millennial‐scale variability of River Ammer floods and its relationship with solar forcing. (12th July 2020) - Rimbu, N.; Lohmann, G.; Ionita, M.; Czymzik, M.; Brauer, A.
Abstract: The relationship between River Ammer flood frequency variability, extreme summer climate over Europe, and solar forcing is investigated. First, we used observational data to evaluate extreme weather and climate anomaly patterns associated with flood and solar forcing as well as the possible dynamical mechanisms behind them. Then, the annual resolution flood layer record from the Lake Ammer sediments is analysed to evaluate millennial‐scale variability of floods and possible related extreme climate patterns back to 5, 500 years BP. A composite analysis reveals that observed River Ammer flood frequency variability at interannual to multidecadal time scales is connected to large‐scale extreme precipitation and temperature patterns. From a synoptic‐scale perspective, the extreme precipitation pattern associated with floods is related to an increase in the frequency of high upper‐level potential vorticity (PV) events over western Europe and a decrease over eastern Europe and western Russia. Increased (decreased) frequency of upper‐level high PV events is related to more (less) surface extreme precipitation occurrence. Furthermore, we show that increased frequency of upper‐level high PV events over western Europe is associated with enhanced blocking activity over eastern Europe. Therefore, the out of phase interannual to millennial‐scale variations of River Ammer flood frequency and solar irradiance, as presented in previous studies, can be explained by a solar modulation of eastern European‐western Russia summer blocking and associated upstream upper‐level wave breaking activity. In addition, we identify two distinct quasi‐periodic signals in both frequency of Lake Ammer flood layer and solar irradiance records with periods of 900 years and 2, 300 years. We argue that similar cycles should dominate millennial‐scale variations of blocking activity in eastern Europe‐western Russia as well as extreme precipitation and flood frequency variability over central and western Europe during the last 5, 500 years. Abstract : Time series of observed River Ammer flood years for the period 1926–1999 AD (blue bars) and years with a flood layer in Lake Ammer sediments (red bars) for the period 3550 BP to 1999 AD show pronounced interannual to millennial scale variations. Part of this variability is related to solar irradiance forcing on atmospheric blocking frequency over Eastern Europe‐western Russia, influencing upper level wave breaking activity and extreme precipitation over western Europe.